Harmonic active vibration control using piezoelectric self-sensing actuation with complete digital compensation. (April 2018) - Pelletier, Anik; Micheau, Philippe; Berry, Alain
In this article, the implementation of a self-sensing piezoelectric actuator with complete digital compensation is presented. The proposed compensation not only minimizes the signal due to the electrical behavior of the self-sensing actuator but also takes into account the fact that piezoelectric actuator causes a local strain—not related to the global vibration of the plate—in a vibrating plate to which it is coupled. Therefore, the corrected measured current is related to the global vibration of the plate and may be used in an active control scheme. The electro-mechanical model on which is based this self-sensing actuator is first explained. Then, the electronic and digital processing implementation is presented, as well as the active time-harmonic control scheme used. Finally, results of experimental validation are presented, and the attenuation performance of the self-sensing actuator is compared to the performances of a co-localized accelerometer/lead zirconate titanate pair. It is shown that the corrected self-sensing actuator current gives results better than what is obtained with a co-localized sensor/actuator pair and that this technique may be used to control more than one frequency simultaneously.